Digital Transformation through Electronic-Based Government System Policy in Indonesia: A Policy Narrative Analysis - Israyudin, Riyan; Arrofi, Fajar Mukhammad; Dwiardi, Agung Rahmat (Journal La Sociale, 2025)
In the era of digital transformation, the Electronic-Based Government System (SPBE) in Indonesia has become a priority to enhance the efficiency and transparency of governance. This study aims to analyze the government's policy narrative on SPBE, compare it with emerging counter-narratives, and formulate strategies to strengthen the policy. Using a post-positivist approach and Narrative Policy Analysis (NPA), data were analyzed from reliable news articles published between 2019 and 2024. The articles were selected from the top three ranked media in Scimago Media Rankings Kompas, Republika, and Okezone ensuring credibility and relevance. The findings indicate that the government's policy narrative emphasizes SPBE as a strategic solution for data integration, cybersecurity enhancement, and improved public service efficiency. The main protagonists of this policy include the Ministry of Administrative and Bureaucratic Reform (PANRB), the National Development Planning Agency (Bappenas), and the Ministry of Communication and Information Technology (Kominfo). However, challenges arise from sectoral egos, technical infrastructure weaknesses such as disruptions in the National Data Center (PDN), and recurring data breaches. Counter-narratives highlight the risks of data centralization and suboptimal inter-agency coordination. The study concludes that strengthening the SPBE policy narrative requires inclusive dialogue, comprehensive evaluations of cybersecurity and infrastructure readiness, and intensive public outreach to build trust and ensure effective policy implementation.